2019
DOI: 10.1002/aorn.12698
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiofrequency Technology on Time Spent Searching for Surgical Sponges and Associated Costs

Abstract: Retained surgical items (eg, sponges, instruments) remain the most frequently reported sentinel events. The primary strategy for preventing retained sponges is the sponge count. Reconciling sponge counts is time consuming and can extend the duration of operative and other invasive procedures. The primary objective of this observational study was to evaluate the effect of a radiofrequency (RF) surgical-sponge detection system on time spent searching for surgical sponges. The study included 27,637 procedures dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…An additional study found that using RF sponge detection technology identified eight near misses and resulted in no RSSs in 27,637 surgeries. 14 This study showed that perioperative team members who used RF technology spent 79.6% less time searching for missing sponges. In addition, there were 71.3% fewer unreconciled counts, and perioperative teams spent 46.3% less time using intraoperative radiographs to identify a retained sponge.…”
Section: Retained Surgical Spongesmentioning
confidence: 84%
See 3 more Smart Citations
“…An additional study found that using RF sponge detection technology identified eight near misses and resulted in no RSSs in 27,637 surgeries. 14 This study showed that perioperative team members who used RF technology spent 79.6% less time searching for missing sponges. In addition, there were 71.3% fewer unreconciled counts, and perioperative teams spent 46.3% less time using intraoperative radiographs to identify a retained sponge.…”
Section: Retained Surgical Spongesmentioning
confidence: 84%
“…An additional study found that using RF sponge detection technology identified eight near misses and resulted in no RSSs in 27,637 surgeries . This study showed that perioperative team members who used RF technology spent 79.6% less time searching for missing sponges.…”
Section: Retained Surgical Spongesmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, implementing and using RF technology routinely may reduce the time that perioperative team members spend reconciling surgical counts. One researcher found that the use of RF technology was associated with nearly 80% less time spent reconciling counts per 1,000 surgical procedures 16 . These data suggest that integrating RF technology into the surgical count process can help perioperative team members resolve miscounts and conserve resources (eg, time, money).…”
Section: Review Of Relevant Evidencementioning
confidence: 99%